TI_GERICHTE 35.2022.64 vom 20. März 2023 , Incidente in scooter. Rendita d'invalidità LAINF: 49% (confermata). IMI complessiva: 60% (confermata) - TI Tribunale d'appello (2023)
Incidente in scooter. Rendita d'invalidità LAINF: 49% (confermata). IMI complessiva: 60% (confermata)